2021
DOI: 10.3390/ijms22189875
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Factors of Takotsubo Syndrome: A Systematic Review

Abstract: Takotsubo syndrome (TTS), recognized as stress’s cardiomyopathy, or as left ventricular apical balloon syndrome in recent years, is a rare pathology, described for the first time by Japanese researchers in 1990. TTS is characterized by an interindividual heterogeneity in onset and progression, and by strong predominance in postmenopausal women. The clear causes of these TTS features are uncertain, given the limited understanding of this intriguing syndrome until now. However, the increasing frequency of TTS ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Two principal studies focused on adrenergic receptor and ESR genes [ 3 ], encoding for the main proteins involved in physiological cardiac function, although conflicting results did not lead to a well-defined picture of the TC pathophysiology. Interestingly, a very recent systematic review has been performed to cast light on the potential genetic and epigenetic factors significantly associated with TC [ 80 ]. The data obtained suggested that genetic variants of ADRB1, GRK5, and BAG3 genes, or variants of APOE, MFGE8, ALB, APOB, SAA1, A2M, and C3 genes, can probably interact with the environment and emotional/physical stress and predispose certain subjects more than others to develop TC.…”
Section: Discussionmentioning
confidence: 99%
“…Two principal studies focused on adrenergic receptor and ESR genes [ 3 ], encoding for the main proteins involved in physiological cardiac function, although conflicting results did not lead to a well-defined picture of the TC pathophysiology. Interestingly, a very recent systematic review has been performed to cast light on the potential genetic and epigenetic factors significantly associated with TC [ 80 ]. The data obtained suggested that genetic variants of ADRB1, GRK5, and BAG3 genes, or variants of APOE, MFGE8, ALB, APOB, SAA1, A2M, and C3 genes, can probably interact with the environment and emotional/physical stress and predispose certain subjects more than others to develop TC.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors TTS may have genetic influences, identified by a limited number of case studies. 33 These studies found TTS to be apparent amongst siblings and parent-child participants. There is a need for larger studies as case study findings may not represent the whole TTS population.…”
Section: Stressmentioning
confidence: 96%
“…TTS may have genetic influences, identified by a limited number of case studies 33 . These studies found TTS to be apparent amongst siblings and parent-child participants.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Currently, a genetic predisposition has been suggested based on several familial TTS cases [124][125][126]. Furthermore, most postmenopausal women experience acute stressful events, but only a small percentage of them will develop TTS.…”
Section: Genetic Factorsmentioning
confidence: 99%